Churnalism and Hype in Science Communication: Comparing University Press Releases and Journalistic Articles in South Africa. Issue 2 (2nd April 2020) - Heyl, Ansa; Joubert, Marina; Guenther, Lars
Abstract: Against the background of a fast-changing media environment and increasing competition in the science arena, we explored how media outlets use science- based press releases issued by research-intensive universities in South Africa. We compared 40 science-related media articles to related institutional press releases. We found that most press releases are re-published with minimal journalistic input and no crediting of the original source, with indications of hype present in a third of the media articles. This could be a reason for concern because press releases issued by research institutions are written to serve the interests of the institution and not to reflect on science. When media outlets re- publish these press releases without editorial input, it means that the critical or investigative role of the media is lost. Given concerns about the long-term implications of churnalism and hype in science media coverage, we ask whether PR-driven communication of science, as practiced by university media offices, among others, serves the long-term interests of science and society. We suggest that universities should consider the options and benefits of moving towards a new science communication paradigm focused less on reputation-building and more on constructive public engagement and helpful dialogue with society.